Calcium hydroxide and porous silicon-impregnated silicon carbide-based composites for thermochemical energy storage. (5th February 2023) - Funayama, Shigehiko; Schmidt, Matthias; Mochizuki, Kyosuke; Linder, Marc; Takasu, Hiroki; Kato, Yukitaka
Highlights: Thermochemical energy storage composites of Ca(OH)2 /porous Si–SiC were developed. The composite with a Si–SiC foam had a volumetric energy density of 0.80 GJ mbed −3 . Its thermal discharge power density was 1.6 times that of pure CaO/Ca(OH)2 powder. The Si–SiC foam composite exhibited a high bulk stability over 15 cycles. Abstract: Thermal energy storage has a prospect for large-scale storage of renewable energy. Thermochemical energy storage using reversible gas–solid reactions can store thermal energy for unlimited periods with high energy density. Calcium hydroxide (Ca(OH)2 ), which is abundant and environmentally friendly, is one of the most promising materials for thermochemical energy storage systems. However, pure Ca(OH)2 powder has poor power density and bulk stability owing to its low thermal conductivity, volume change, and agglomeration over dehydration–rehydration cycles. Practical composites that can simultaneously overcome these problems have not been reported yet. This study combines Ca(OH)2 with ceramic foam and honeycomb structures of silicon-impregnated silicon carbide (Si–SiC) and demonstrates the improved power density and bulk stability of the resulting composites. The Si–SiC foam composite, loaded in a laboratory-scale fixed-bed reactor, exhibits a thermal discharging power density of 0.71 MW mbed −3, which is 1.6 times that of the pure Ca(OH)2 powder. In addition, the foam composite reduces the volume change by 80% and does not form centimeter-scale agglomerates even after 15 cycles, unlike the pure powder. The results suggest that embedding solid storage materials into thermally conductive open-cell foams can simultaneously enhance power density and bulk stability.